Estudo da eficiência de diferentes fontes de fosfato na cultura do sorgo cultivado em Cambissolo. - Lima, Izabel Maria Almeida (2013)
The low available phosphorus in tropical soils generally require constant research regarding the efficiency and the application of different sources of phosphate fertilizers on crops. This work aimed to study the responses of sorghum (Sorghum bicolor) to applications of different levels and sources of phosphorus in terms of growth, yield and nutrient removal, and also to evaluate the agronomic efficiency of these different sources. The experiment was conducted under greenhouse conditions at the Federal University of Ceará, Brazil. It was used a Cambisol soil from the Chapada do Apodi-CE. The statistical design consisted of a randomized complete block in a 4x4 factorial (rates and sources of P, respectively), with treatments consisting of a combination of four rates of phosphorus (rate 1 = 0 mg P kg-1 soil, rate 2 = 100 mg P kg-1 soil, rate 3 = 200 mg kg-1, rate 4 = 300 mg P kg-1 soil) with 4 replicates, totalizing 64 experimental units; it was used four sources of P (Phosphate Industrial Triple superphosphate - TS, Natural Phosphate of Bahia - NFB, Natural Phosphate of Tocantins - NPT and Natural Reactive phosphate - Gafsa - NRP). The following variables were evaluated: plant height, stem diameter, dry shoot matter production and, macronutrients and micronutrients leaf concentrations. The variables value results were subjected to analysis of variance (ANOVA), regression analysis according to sources and increasing rates of phosphorus; the averages of these variables were evaluated by the Tukey test at 5% probability. The TS and the NFB sources were responsible for the higher significant responses of the biometric variables studied, whereas NPT induced the lowest responses. The sources that contributed most to the plant absorption of soil phosphorus by sorghum were in descending order: TS > NFB > NRP > NPT. In the rate 300 mg kg-1solo occurred the most elevated macronutrient and micronutrient plant P uptake. Considering the amounts of macronutrients and micronutrients absorbed by sorghum, in function of rates and P sources, these occurred in the following order: N > K > Ca > Mg > P > S (macronutrients); Mn > Fe > Zn > Cu (micronutrients). The source that had the highest index of Agronomic Efficiency was the Triple superphosphate, followed by the Natural phosphate of Bahia.